A Systematic Review of the Electrodiagnostic Assessment of Neonatal Brachial Plexus - Orozco, Virginia (Neurol Neurobiol (Tallinn), 2020)
Despite improvements in obstetric care, neonatal brachial plexus palsy continues to significantly impact infants’ lives worldwide, with an incidence of 1 to 4 per 1000 live births. While a majority of affected infants recover spontaneously by three months, 20-30% suffer permanent functional deficits that significantly impair their quality of life. Anatomical complexity of the brachial plexus results in varying degrees of injury and pathological changes at multiple levels within the plexus. Current clinical diagnosis relies on electrodiagnostic techniques such as nerve conduction (i.e., motor and sensory) and electromyography studies. These techniques not only aid clinicians to differentiate between axonal and demyelinating lesions, evident by changes in signal shape and conduction, but also provide prognostic information in cases of brachial plexus injuries. The presented study offers a comprehensive review of existing literature on electrodiagnostic techniques employed for assessing neonatal brachial plexus injuries.